Predictive Value of Inflammatory Cytokines in Early Pregnancy for Liver Dysfunction in Pregnant Women with Hepatitis B - Wang, Wei; Jia, Hongyan; Wang, Yue; Sun, Weize; Yang, Can (Hormone and Metabolic Research, 2022)
The purpose of this study is to explore the predictive value of cytokine levels in the first trimester of pregnancy on abnormal liver function of pregnant women with hepatitis B in the third trimester of pregnancy. A total of 111 pregnant women with HBV infection at 12 weeks gestation participated in the study. The levels of IL-6, IL-8, TNF-α in peripheral blood of the patients and liver function indexes were detected. Subsequently, the pregnant women were followed up, and the liver function was detected at 36 weeks of gestation. According to liver function indexes, patients were divided into normal liver function group and abnormal liver function group to determine the correlation between cytokines in early pregnancy and abnormal liver function in late pregnancy. Kaplan–Meier survival curve and multivariate Cox analysis were used to evaluate the predictive value of cytokines for liver dysfunction. At 12 weeks of gestation, cytokine levels in the normal liver function group were significantly lower than that in the abnormal liver function group. Kaplan–Meier survival analysis showed that the increased IL-6 level was associated with abnormal liver function in late pregnancy. Multivariate Cox regression analysis revealed that IL-6 level was an independent predictor of abnormal liver function in patients with normal liver function in the late pregnancy. The high expression level of cytokine IL-6 at 12 weeks of pregnancy has noteworthy predictive significance for the abnormal liver function of hepatitis B pregnant women in third trimester of pregnancy.
Keywords: pregnancy; hepatitis b virus; liver function; cytokines